ChemInform Abstract: Ordered Mesoporous Materials Based on Interfacial Assembly and Engineering. Issue 48 (26th November 2013) - Li, Wei; Yue, Qin; Deng, Yonghui; Zhao, Dongyuan
Abstract Review: 249 refs.